2023
DOI: 10.1021/acs.jmedchem.2c01115
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activity of Marinacarboline Analogues as STAT3 Pathway Inhibitors for Docetaxel-Resistant Triple-Negative Breast Cancer

Abstract: Metastatic triple-negative breast cancer (mTNBC) is a fatal type of breast cancer (BC), and signal transducer and activator of transcription 3 (STAT3) has emerged as an effective target for mTNBC. In the present study, compound MC0704 was found to be a novel synthetic STAT3 pathway inhibitor, and its potential antitumor activity was demonstrated using in vitro and in vivo models in docetaxel-resistant TNBC cells. Based on marinacarboline (MC), a series β-carboline derivatives were synthesized and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Recently, aberrant activation of STAT3 has been considered to be correlated with acquired drug resistance. , Interestingly, HCT116-5-FU cells also exhibited hyperactivation of STAT3 compared to their parent HCT116 cells. However, lenziamide A treatment for 24 h effectively suppressed p-STAT3 expression in HCT116-5-FU cells, indicating the possibility of overcoming acquired anticancer drug resistance in CRCs (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, aberrant activation of STAT3 has been considered to be correlated with acquired drug resistance. , Interestingly, HCT116-5-FU cells also exhibited hyperactivation of STAT3 compared to their parent HCT116 cells. However, lenziamide A treatment for 24 h effectively suppressed p-STAT3 expression in HCT116-5-FU cells, indicating the possibility of overcoming acquired anticancer drug resistance in CRCs (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have demonstrated Napabucasin’s capability to reduce TNBC cell viability ( 156 ). Additionally, a series of compounds, such as 7a ( 157 ), SLSI-1216 ( 158 ), H182 ( 159 ), SMY002 ( 160 ), MC0704 ( 161 ), ZSW ( 162 ), and Acetyl-cinobufagin ( 163 ), have been identified to selectively inhibit STAT3 phosphorylation by binding to its SH2 domain and suppressing TNBC cell viability in vitro . Arctigenin, a bioactive lignan isolated from the seeds of Arctium lappa, inhibits STAT3 in TNBC cells by binding to its SH2 domain, thereby disrupting hydrogen bond connections between DNA and STAT3.…”
Section: Current Therapeutic Applications Of the Jak2/stat3 Signaling...mentioning
confidence: 99%
“…Marinacarbolines A–D ( 263 – 266 ), obtained from Marinactinospora thermotolerant , and their synthetical derivatives, bear an additional C3-amido moiety with pendant aryl rings ( Figure 54 ). Their cytotoxicity was first investigated in 2015 [ 190 ] , but Hong and Lee have performed a very recent and in-depth SAR study against ocetaxel-Resistant Triple-Negative Breast Cancer [ 191 ]. Compounds 263 – 266 also exhibit promising antimalarial activity [ 129 ].…”
Section: Marine Indole Alkaloidsmentioning
confidence: 99%
“…Penerpenes A-B (190,191) are two indole diterpenoids obtained from Penicillium sp. KFD28, isolated from a bivalve mollusk.…”
Section: Other Polycyclic Indole Alkaloidsmentioning
confidence: 99%